Factors Affecting The Income Of Pennyakap Red Onion Farmers In Tampo Village, Anggeraja Sub-District, Enrekang District. - Reni, Reni; Idrus Salam; Wa Ode Yusria (International journal of technology and education research, 2023)
Shallots are a horticultural plant of the spice vegetable group with high economic value. The cultivation of shallot commodities is thought to increase income and improve welfare. However, on the other hand, there are several problems that occur in farmers where the income of farmers does not always increase, this is because there are several factors that affect the size of income.This study aims to determine how much income is obtained by orangutan farmers from onion farming in Tampo Village, Anggeraja District, Enrekang Regency and how the effect of production costs, production amount, selling price and labor on the income of shallot trapping farmers in Tampo Village , Anggeraja District, Enrekang Regency. The sampling technique used was simple random sampling from 44 farmers. This research uses qualitative analysis methods, quantitative description and multiple linear regression analysis. The results of this study showed that based on income analysis, the average yield of receipts (TR) of one planting season per farmer was obtained, which was IDR 252,698,634. Based on the results of regression, which has a significant effect, namely production costs, production quantities, and selling prices. meanwhile